COVID-19 Pandemic and Mental Health Law in Indonesia: A Review of Regulations and Implementation Challenges - Ridwan Ridwan; Ifan Sadewa; Karomah Alif Sabilla Rustam Sutoto (Siber Nusantara of Law and Politic Review, 2024)
The COVID-19 pandemic has had a significant impact on the mental health of people worldwide, including in Indonesia. This article aims to explore and examine the relationship between the COVID-19 pandemic and the legal policies governing mental health in Indonesia. Using a qualitative approach through literature review and legislation, this article highlights the main challenges in the implementation of mental health law during the pandemic, such as social stigma, limited access to mental health services, and a lack of resources. In addition, the opportunity for integrating community-based mental health services was also discussed as a reform step. Through this analysis, it is hoped that solutions can be found to strengthen the legal framework that supports mental health more effectively, including recommendations for policy improvements and implementation strategies for the future. Research findings indicate that policy reform and improved accessibility to mental health services are crucial steps for enhancing the mental well-being of the community during the pandemic.